Patient-centeredness-a cultural targeted survey among junior medical managers - Orna Tal; Royi Barnea; Aviad Tur-Sinai (BMC, 2023)
Abstract Background Patient-centeredness is a core element in healthcare. However, there is a gap between the understanding of this term by healthcare professionals, and patients' capability, self-efficacy, and willingness to take part in medical decisions. We aim to expose standpoints toward "patient centeredness" among junior medical managers (JMM), as they bridge between policy strategies and patients. We try to reveal cultural differences by comparing the views of the majority and the minority subpopulations of Israel (Arabic and Hebrew speakers). Methods A cross-sectional survey among JMM studying for an advanced degree in health-system management at three academic training colleges in Israel was conducted in February-March 2022. The respondents completed a structured questionnaire comprising four sections: a) perceptions of trust, accountability, insurance coverage, and economic status; b) perceptions regarding decision-making mechanisms; c) preferences toward achieving equity, and d) demographic details. Results A total of 192 respondents were included in the study-50% Hebrew speakers and 50% Arabic speakers. No differences were found between Arabic and Hebrew speakers regarding perception of trust, accountability, insurance coverage, and economic status. JMM from both subpopulations believed that patients' gender and age do not influence physicians' attitudes but Arabic-speaking respondents perceived that healthcare professionals prefer educated patients or those with supportive families. All respondents believed that patients would like to be more involved in medical decisions; yet Arabic-speakers perceived patients as tending to rely on physicians' recommendations while Hebrew speakers believed that patients wish to lead the medical decision by themselves. Conclusions Patient-centeredness strategy needs to be implemented bottom-up as well as top-down, in a transparent nationwide manner. JMM are key actors in carrying out this strategy because they realize policy guidelines in the context of social disparities, enabling them to achieve a friendly personalized dialogue with their patients. We believe that empowering these JMM may create a ripple effect, yielding a bottom-up perception of equity and initiating change.